Potential threats of environmental microplastics to the skeletal system: current insights and future directions - Zhao, Haofan; Mu, Sirong; Wang, Weizhou; Li, Xi (Frontiers in Endocrinology, 2025)
Micro- and nanoplastics (MNPs), as emerging environmental pollutants, have attracted global attention due to their pervasive presence in ecosystems and human living environments. Plastic additives confer high durability, and MNPs derived from environmental degradation can enter the human body via inhalation or ingestion. Smaller particles are capable of penetrating biological barriers and accumulating in various tissues. Recent studies have revealed that beyond their known accumulation in the digestive, respiratory, and reproductive systems, MNPs may also reach the bone microenvironment via systemic circulation. The bone microenvironment, composed of diverse cell types and extracellular matrix components, is essential for maintaining bone formation, remodeling, and immune regulation. Emerging evidence indicates that MNPs can infiltrate the bone marrow, disrupt its homeostasis, and accumulate within the musculoskeletal system, potentially impairing bone metabolism and function. This review summarizes the sources and metabolic pathways of MNPs and elucidates their impact on the bone microenvironment, with a focus on mechanisms involving chemical toxicity, inflammation, and metabolic dysregulation. The findings provide a theoretical foundation and research direction for evaluating the risks of MNPs exposure to skeletal health.